The Correlation Between Burnout and Religious Coping Strategies Among Healthcare Workers at Bombana General Hospital - Andreani, Robertha Lutfi; Anggia Dwi Stephanie Tandipayuk; Obed Paundralingga; Santiwati Anda; Ronny Tri Wirasto; Silas Henry Ismanto (Faculty of Medicine, Universitas Airlangga, 2026)
Introduction: Burnout, also known as professional fatigue syndrome, results from prolonged stress in the workplace. Healthcare workers are particularly vulnerable to burnout and depression due to the nature of their work, which often involves intensive and ongoing interactions with others, such as in service delivery. Identifying workplace stressors is essential in mitigating their effects for psychological well-being. Spiritual coping is one effective way to deal with stress. Methods: This study was conducted from July to October 2024 among healthcare workers at Bombana Regional General Hospital (RSUD Bombana). The sampling technique used was purposive sampling. Burnout was assessed using the Maslach Burnout Inventory, while religious coping strategies were measured using the Brief R-Cope. Data analysis employed the Spearman correlation test (p<0.05). Results: A total of 86 healthcare workers met the study criteria. A significant correlation was found between negative religious coping (NRC) and burnout, with higher NRC usage correlating with greater burnout levels (p=0.014, r=0.264). However, no significant correlation was observed between positive religious coping (PRC) and burnout, indicating that PRC did not influence burnout levels in the respondents of this study (p=0.335, r=0.105). Conclusion: Individuals with high levels of positive religiosity do not experience burnout. Religious coping strategies help individuals utilize faith and religious practices to manage stress and acquire meaning in difficult circumstances.